Comparative radiation performance of different feeding technique for a microstrip patch antenna - P. J. Soh, author; Mohd. Kamal A. Rahim, author; Aahari Asrokin, author; Mohd Zainol Abidin, author; Abdul Aziz, author; Asia-Pasific Conference on Applied Electromagnetics (2005 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2005)
PSZJBL